Processus de gestion des ressources éducatives. Le cas d'enseignants en IUT - Cécile Redondo; Rémi Cadet; Romain Perrier; Béatrice Drot-Delange
The aim of our study is to understand the activities carried out by university institute of technology teachers in preparing their courses using educational resources. It also aims to identify what constitutes an educational resource for these teachers. We are wondering whether any specific features emerge from the teachers' necessary and strong relationship with the economic sector. Four streams are studied: biological engineering, business and administration management, computer science and multimedia and Internet professions. Taking as our starting point the characterization of processes already identified among teachers in technological secondary education, we identify, through the analysis of semi-structured interviews, four processes at work among the teachers: transmission-inheritance, collection of resources, constitution of a network of trust, i.e. recognition of the reliability and/or relevance of a resource, and participation in resource-producing collectives. A coding grid for the interviews is established, with the semantic unit as the chosen coding unit. While the analysis of the interviews reveals differences depending on the channel, the process of building a network of trust is predominantly present. We compare our results with those of questionnaire surveys on teachers' practices in university teaching.